Architectural fashion. - Sarah Zainal Abidin. (2012)
Since medieval times, fashion has been inspired and influenced by architecture contemporary to its era, leading to an infusion of architectural elements and the structure of garments. In this project, drawing references from several contemporary architects and their works, I aim to create garments that are avant-garde by reinterpreting the form of the female body with abstracted architectural elements. A gradual change in the shape of these outfits will be presented as a sequence, showing the flow of garments morphing from one shape to another.